Comparative cardiomyocyte differentiation potential of rat adipose-derived mesenchymal stem cells from two anatomical sites: metabolomic profiling and pathway analysis - Farag, Ahmed; Samir, Haney; Koung Ngeun, Sai; Kaneda, Masahiro; Hendawy, Hanan; Takahashi, Ken; Tanaka, Ryou (Frontiers in Cell and Developmental Biology, 2025)
BackgroundAdipose-derived mesenchymal stem cells (AD-MSCs) have emerged as a promising source for cardiac regenerative therapy due to their multipotency and ease of isolation. However, the impact of anatomical origin on their cardiomyocyte differentiation potential remains unclear. Metabolic analysis provides valuable real-time insights into the cellular metabolic state, capturing dynamic changes in metabolite concentrations that reflect both internal cellular mechanisms and external stimuli. This approach allows us to identify specific metabolic pathways activated during cardiomyocyte differentiation, offering a deeper understanding of how the anatomical origin of stem cells influences their differentiation potential and metabolic flexibility. Such insights are critical for optimizing stem cell-based therapies for cardiac regeneration. This study aimed to compare the differentiation capacity of AD-MSCs derived from peri-ovarian and peri-renal adipose tissue, with a focus on metabolic adaptations during cardiomyocyte differentiation.MethodsAD-MSCs were isolated from peri-ovarian and peri-renal fat of Sprague-Dawley rats and characterized by morphology, immunophenotyping, and multilineage differentiation potential. Cardiomyocyte differentiation was induced using 5-azacytidine, and morphological changes were assessed via phase-contrast microscopy and immunofluorescence staining for cardiac troponin T (cTnT). Untargeted metabolomic profiling was performed using gas chromatography-mass spectrometry (GC-MS), followed by principal component analysis (PCA), partial least squares discriminant analysis (PLS-DA), and pathway enrichment analysis.ResultsBoth peri-ovarian and peri-renal AD-MSCs exhibited similar fibroblast-like morphology, MSC-specific marker expression (CD44, CD90, CD29), and multilineage differentiation potential. Following cardiomyocyte induction, both groups displayed morphological changes indicative of differentiation and strong cTnT expression. Metabolomic analysis of the cardiogenic differentiation samples identified distinct metabolic adaptations between the two AD-MSC sources. Peri-ovarian AD-MSCs exhibited a broader metabolic reprogramming, with increased engagement of glycolysis, fructose metabolism, glycerolipid metabolism, and the TCA cycle, suggesting enhanced metabolic flexibility and energy efficiency. In contrast, peri-renal AD-MSCs relied more on galactose metabolism, indicating an alternative energy strategy during differentiation.ConclusionThe anatomical origin of AD-MSCs influences their metabolic landscape during cardiomyocyte differentiation. Peri-ovarian AD-MSCs demonstrated greater metabolic adaptability, potentially favoring their differentiation capacity, making them a promising candidate for cardiac regenerative applications.